Pengaruh Environmental Performance Terhadap Environmental Disclosure dan Economic Performance (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di BEJ Periode 2001 - 2004) - Suratno, Ignatius Bondan; Darsono, Darsono; Mutmainah, Siti (The Indonesian Journal of Accounting Research, 2007)
A purpose of this study is to examine an impact of environmental performance on an environmental disclosure and on economic performance. This study is not in line with an Al-Tuwaijri's model (2004), by stressing more on an impact of independent variable to dependent variable.This study is based on a longitudinal empirical applied research. Through a judgment sampling technique, 19 public companies which participated in the PROPER program from 2002-2005 were included in the research.Â  First, the data were tested using the Hausman test. Because the simultaneous relation on environmental performance and economic performance isn't statistically significant, afterwards the data were test using ordinary least squares.The test result for the first hyphotesis is indicated that the impact of environmental performance to environmental disclosure is positive and statistically significant. The test result for the second hyphotesis is indicated that the impact of environmental performance to environmental disclosure is positive statistically significant. Thus, all of the test result are a support for the finding of Al-Tuwaijri, et al. (2004).